Erythema ab igne with features resembling keratosis lichenoides chronica. (5th November 2020) - Wells, Amy; Desai, Anand; Rudnick, Eric W.; Motaparthi, Kiran
Abstract: Erythema ab igne (EAI) is an asymptomatic dermatosis that develops in response to chronic exposure to low‐grade heat. Characteristic findings on histopathology include epidermal atrophy, dermal elastosis, atypical histiocytes, and melanin and hemosiderin deposition. Reactive endothelial changes and prominent vascular proliferation are variable. Keratosis lichenoides chronica (KLC) is a rare lichenoid hyperkeratotic dermatosis. Acanthosis with parakeratosis and a lichenoid interface dermatitis with lymphocytes, histiocytes, and plasma cells are characteristic findings of KLC. Although its etiology remains unclear, KLC has been reported to occur in response to heat. Herein, we report a case of EAI with features resembling KLC.